Study of the kinetics structure formation of cement dispersed systems. Part I - Evgenij V. Korolev; Anna N. Grishina; Aleksandr S. Inozemtcev; Arkady M. Ayzenshtadt (Нанотехнологии в строительстве, 2022)
Introduction. The study of the kinetics structure formation is rarely the subject of a careful study. Although it is important for materials used to create elements of building structures, energy elements, thermoelements and materials for other purposes. The article proposes refinements of the methodology for determining the parameters of the kinetics structure formation of cement composites, including modified compositions. Methods and materials. The structure formation of cement systems with plasticizers, microsized mineral additives (hydrosilicates of barium, copper and zinc) and nanosized particles of zinc hydrosilicates has been studied. Results and discussion. It is proposed to single out two stages of initial structure formation: the stage of setting the cement paste and the stage of hardening. The selection of the setting stage is connected with the natural laws of the development of natural systems, namely, the initial formation of a structural grid obeys an exponential law. Moment of time when a deviation from this law is observed is the time of occurrence of spatial and/or prescription difficulties that hinder the exponential development of the system. Conclusions. A strong negative relationship between the parameters φ and β of the equation H(t) = a exp(φt β) has been established. These parameters characterize the rate of structure formation at the setting stage (parameter φ) and the density of the structure (parameter β or the internal dimension Di, 0 associated with it). The presence of such a negative relationship indicates the inadvisability of accelerating the processes of structure formation at the stage of setting. This is supported by a strong positive relationship between the period of initial structure formation t0, s1 and the strength of the material R28.